Evaluation of profibrotic gene transcription in renal tissues from cats with naturally occurring chronic kidney disease. (29th May 2020) - Lourenço, Bianca N.; Coleman, Amanda E.; Tarigo, Jaime L.; Berghaus, Roy D.; Brown, Cathy A.; Rissi, Daniel R.; Stanton, James B.; Brown, Scott A.; Schmiedt, Chad W.
Abstract: Background: Increased gene transcription of hypoxia‐induced mediators of fibrosis in renal tissue has been identified in experimentally induced, ischemic chronic kidney disease (CKD). Objective: To characterize hypoxia‐induced profibrotic pathways in naturally occurring CKD in cats. Animals: Twelve client‐owned cats with CKD and 8 healthy control cats. Methods: In this prospective, cross‐sectional study, bilateral renal tissue samples were assessed histologically for inflammation, tubular atrophy, and fibrosis, and by reverse transcription‐quantitative PCR for characterization of transcript levels of hypoxia‐inducible factor‐1α ( HIF1A ), matrix metalloproteinases‐2 ( MMP2 ), ‐7 ( MMP7 ), and ‐9 ( MMP9 ), tissue inhibitor of metalloproteinase‐1 (TIMP1), transforming growth factor‐β1 ( TGFB1 ), and vascular endothelial growth factor‐A ( VEGFA ). Linear mixed models were used to compare gene transcription between diseased and healthy kidneys, and to examine the association between transcript levels and serum creatinine concentration for all cats, and between transcript levels and histologic scores of diseased kidneys. Results: Kidneys from cats with CKD had significantly higher transcript levels of HIF1A, MMP2, MMP7, MMP9, TIMP1, and TGFB1 (all P < .001), and lower levels of VEGFA ( P = .006) than those from control cats. Transcript levels of MMP7 ( P = .05) and TIMP1 ( P = .005) were positively associated with serum creatinine in cats with CKD, but not in control cats. In diseased kidneys, transcript levels of MMP2 ( P = .002), MMP7 ( P = .02), and TIMP1 ( P = .02) were positively, whereas those of VEGFA ( P = .003) were negatively, associated with histologic score severity. Conclusion and Clinical Significance: Evaluation of the expression of the corresponding proteins in larger populations could identify therapeutic targets and/or biomarkers of tubulointerstitial fibrosis in cats.